Associations between fetal size, maternal α-tocopherol and childhood asthma. Issue 5 (30th April 2010) - Turner, Stephen W; Campbell, Doris; Smith, Norman; Craig, Leone C A; McNeill, Geraldine; Forbes, Sarah H; Harbour, Paul J; Seaton, Anthony; Helms, Peter J; Devereux, Graham S
Abstract : Background: The origins of respiratory disease might be traced back to exposures during fetal life. The aim of the present study was to explore whether there was a relationship between fetal size and respiratory outcomes at 5 years of age in the context of fetal exposure to vitamin E. Methods: A longitudinal birth cohort study was recruited (n=1924). Antenatal ultrasound scan results were identified and the following recorded: crown–rump length (CRL) in the first trimester; femur length (FL) and biparietal diameter (BPD) in the second trimester. Maternal plasma α-tocopherol (vitamin E) was measured at the time of the first trimester scan. At 5 years, wheeze and asthma symptoms were reported by questionnaire, and spirometry was measured. Results: CRL, spirometry and questionnaire data at 5 years were available for 835, 579 and 1145 individuals, respectively. There were positive associations between CRL and forced expiratory volume in 1 s (FEV1 ; 5 ml increase in FEV1 per mm CRL, p=0.001, n=283), forced vital capacity (FVC; 6 ml increase in FVC per mm CRL, p=0.001) and forced expiratory flow between 25% and 75% of FVC (FEF25–75 ; 0.008 ml/s increase in FEF25–75 per mm CRL, p=0.023), and inverse relationships with CRL and current wheeze (OR 0.59 per CRL quartile, p=0.026, n=547) and asthma (OR 0.55 per CRL quartile p=0.011). CRL was positively associated with maternal plasma α-tocopherol (p=0.002). Conclusions: These findings support the concept of very early fetal programming of respiratory disease. Maternal vitamin E status may be one determinant for growth of the fetus and fetal lungs during early pregnancy.